2013
DOI: 10.1080/13683500.2013.786027
|View full text |Cite
|
Sign up to set email alerts
|

How ecotourism works at the community-level: the case of whale-watching in the Azores

Abstract: Whale-watching is one of the fastest growing tourism industries worldwide, often viewed as a sustainable, non-consumptive strategy for the benefits of cetacean conservation and the coastal communities, alternative to and incompatible with whaling. Yet there is paucity of research on how things actually work out at the community-level. Drawing on research literature and my own ethnographic fieldwork, this article bridges a knowledge gap in this field while examining an Azorean context where tourism has brought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 59 publications
2
16
0
3
Order By: Relevance
“…These tourism practices have been considered socio-economically successful and ecologically sustainable in the shortterm (Burgin and Hardiman, 2015) based on loose definitions and contextual goals. However, there is considerable controversy now surrounding many of these ventures because of their impacts on habitat and/or species involved (Silva, 2015). Although the changes observed are often classified as case-specific or temporary (Apps et al, 2015;Barker et al, 2011a), the continuous presence and cumulative effect of such negative impacts is likely to have long-term consequences (Barker et al, 2011b) such as decrease in health or reproductive fitness (e.g.…”
Section: Impacts Of Marine Wildlife Tourismmentioning
confidence: 99%
“…These tourism practices have been considered socio-economically successful and ecologically sustainable in the shortterm (Burgin and Hardiman, 2015) based on loose definitions and contextual goals. However, there is considerable controversy now surrounding many of these ventures because of their impacts on habitat and/or species involved (Silva, 2015). Although the changes observed are often classified as case-specific or temporary (Apps et al, 2015;Barker et al, 2011a), the continuous presence and cumulative effect of such negative impacts is likely to have long-term consequences (Barker et al, 2011b) such as decrease in health or reproductive fitness (e.g.…”
Section: Impacts Of Marine Wildlife Tourismmentioning
confidence: 99%
“…Yet, research has shown that, in spite of the positive effects that it may have in some cases, tourism is not a remedy to the problems facing rural areas, that not all rural spaces are suitable for the development of tourism and, similarly, that tourism development often fails to stimulate the anticipated socioeconomic revitalisation (e.g. Iorio and Corsale, 2010;OECD, 1994;Silva, 2015;Walmsley, 2003). National identity is commonly described in the scholarly literature as an individual identification and as a specific form of collective identity, in the construction of which the existence of a common past plays a critical role (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…a use of a resource in ways that do not reduce its supply. Some authors have questioned the use of the term 'non-consumptive' in the context of whale watching (see [94] for a discussion on this issue) since there is evidence that the intensification of whale-watching activities may have a negative impact on cetaceans, altering their short and/or long-term behavior patterns and leading to displacement, progressively affecting the animals’ health and therefore their survival [9598]. Current conservation measures should therefore include not only population management, but also the management/regulation/control of human activities that can affect whales and dolphins.…”
Section: Introductionmentioning
confidence: 99%